2020
DOI: 10.3389/fmolb.2020.00100
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Folding and Binding Probed by Systematic Non-canonical Mutagenesis

Abstract: Many proteins and peptides fold upon binding another protein. Mutagenesis has proved an essential tool in the study of these multi-step molecular recognition processes. By comparing the biophysical behavior of carefully selected mutants, the concert of interactions and conformational changes that occur during folding and binding can be separated and assessed. Recently, this mutagenesis approach has been radically expanded by deep mutational scanning methods, which allow for many thousands of mutations to be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Both disulfide reduction and D101N mutations are either within the loops or close to the loop regions, so the anti-cooperative effect may be due to the loop structures having conformational ensembles that are modified by mutation or disulfide reduction. Previous studies have shown that mutation could affect cooperative folding ( Batey et al, 2005 ; Rogers, 2020 ) and that disordered structures (such as disordered loops) could affect long-range ( 10 nm) cooperative folding ( Gruszka et al, 2016 ). In the disulfide-reduced and D101N variants, well-structured loops in chain A may strain the native structure of chain B so that loop disorder is enhanced for chain B in the context of the dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Both disulfide reduction and D101N mutations are either within the loops or close to the loop regions, so the anti-cooperative effect may be due to the loop structures having conformational ensembles that are modified by mutation or disulfide reduction. Previous studies have shown that mutation could affect cooperative folding ( Batey et al, 2005 ; Rogers, 2020 ) and that disordered structures (such as disordered loops) could affect long-range ( 10 nm) cooperative folding ( Gruszka et al, 2016 ). In the disulfide-reduced and D101N variants, well-structured loops in chain A may strain the native structure of chain B so that loop disorder is enhanced for chain B in the context of the dimer.…”
Section: Discussionmentioning
confidence: 99%
“…The cyanogen bromide treatment in 70% formic acid provides fully denaturing conditions, which may cause peptide folding issues. It can be expected that soluble peptide would fold properly on its substrate [37] , especially if it is acysteine-free peptide. Enfuvirtide is exceptionally well-studied peptide.…”
Section: Discussionmentioning
confidence: 99%